PENERAPAN METODE PERAMALAN SEBAGAI UPAYA MENGURANGI BULLWHIP EFFECT PADA UMKM PENTOL X - Apsari Puspitaningtyas; Muslimin Abdulrahim (LPPM Universitas Bina Bangsa, 2023)
Every business is required to improve the things in it so that it continues to survive and develop. Proper management is needed in every business to develop business performance. Pentol X UMKM is an MSME that was founded in 2018. Fluctuations in demand cause stock instability so that there is over stock and also lack of stock and indicates a bullwhip effect. Based on the problems that occur, an approach will be taken to solve this problem by using four forecasting methods, namely Moving Average, Single Exponential Smoothing, Double Exponential Smoothing, Triple Exponential Smoothing. Based on the research results, the forecasting method used for large pentol products is Triple Exponential Smoothing Multiplicative. The forecasting method used for small bulb products is Triple Exponential Smoothing Multiplicative. The forecasting method used for tofu products is Triple Exponential Smoothing Additive. The results of the research show that the value of the bullwhip can be reduced